REVIEW OF COMPLETE HAEMOGRAM REPORTS AND MORPHOLOGICAL CLASSIFICATION OF ANEMIA (CIPEEX, 2022)
THE WORLD HEALTH ORGANIZATION (WHO) DEFINES ANEMIA AS "A STATE IN WHICH THE BLOOD HEMOGLOBIN CONCENTRATION IS ABNORMALLY LOW AS A RESULT OF THE LACK OF ONE OR MORE ESSENTIAL NUTRIENTS, WHATEVER THE SOURCE OF THE DEFICIENCY." FOR THE DIAGNOSIS OF ANEMIA THE HEMOGRAM IS USED, WHICH IS A LABORATORY EXAMINATION FOR QUANTITATIVE AND QUALITATIVE ANALYSIS. THE DATA PROVIDED BY THE HEMOGRAM ARE FUNDAMENTAL IN THE INVESTIGATION OF HEMATOLOGICAL DISEASES. THE USE OF HEMATIMETRIC INDEXES IS OF GREAT IMPORTANCE TO RATIONALIZE THE DIFFERENTIAL DIAGNOSIS OF ANEMIA, SUCH AS MEAN CORPUSCULAR VOLUME (MCV), MEAN CORPUSCULAR HEMOGLOBIN (HCM), AND MEAN CORPUSCULAR HEMOGLOBIN CONCENTRATION (CHCM). THE OBJECTIVE WAS TO CARRY OUT A SURVEY OF THE COMPLETE BLOOD COUNT REPORTS, WITH THE PURPOSE OF EVALUATING THE PREVALENCE OF ANEMIA ACCORDING TO THE MORPHOLOGICAL CLASSIFICATION STRATIFYING THEM IN VARIABLES OF GENDER AND AGE GROUP. IT IS A RETROSPECTIVE LONGITUDINAL STUDY, IN WHICH THE REPORTS OF COMPLETE BLOOD COUNT OF PATIENTS ATTENDED BY SUS WERE ANALYZED IN THE CITY OF ANÁPOLIS - GOIS - BRAZIL. THE REPORTS WERE COLLECTED AT THE LABORATORY OF CLINICAL ANALYZES OF UNIEVANGLICA, DURING THE PERIOD 01/01/2017 TO 08/08/2017. THE DATA WERE COLLECTED FROM THE LABORATORY RECORD AND THE REPORTS FILE BY THE INTERNAL SYSTEM ( SISLAC), THE RESULTS WERE THEN TRANSCRIBED INTO AN EXCEL TABLE FOR FURTHER DATA ANALYSIS. THE WORK WAS APPROVED BY THE RESEARCH ETHICS COMMITTEE OF THE INSTITUTION UNDER PROTOCOL NUMBER: 2,675,303 / 2018. A TOTAL OF 2,023 BLOOD CELL COUNTS WERE ANALYZED AT UNIEVANGLICA'S CLINICAL ANALYZES LABORATORY IN 2017. THE STUDY FOUND A DECREASE IN HEMOGLOBIN IN 20.61% OF THE PATIENTS, WHICH IS INDICATIVE OF ANEMIA (417 / 2,023). NORMOCYTIC ANEMIA WAS THE MOST PREVALENT IN THE STUDY POPULATION AND WAS PRESENT IN 72.4% OF THE ANEMIC REPORTS (302/417). NORMOCYTIC AND HYPOCHROMIC ANEMIAS WERE OBSERVED IN 34.4% (104/302), THE MORPHOLOGY AND STAINING OF RED BLOOD CELLS WITHIN THE NORMALITY PARAMETERS VISUALIZED IN 65.5% OF THE REPORTS (198/302). OF THE PATIENTS PRESENTING ANEMIA AT COLLECTION, 109 HAD MICROCYTOSIS REPRESENTING 24.22% OF THE TOTAL ANEMIA (109/417). MICROCYTIC AND HYPOCHROMIC ANEMIA WERE PRESENT IN 92.6% OF THE CASES (101/109), WHILE MICROCYTIC AND NORMOCRMIC ANEMIA WERE OBSERVED IN 7.4% (8/109). INTERESTINGLY, MACROCYTIC ANEMIA WAS A POORLY REPORTED EVENT, BEING PRESENT IN 1.4% OF THE REPORTS (6/417), ALL OF WHICH HAD NORMOCROMIC ERYTHROCYTES. AMONG THE ANEMIC PATIENTS, 54.7% OF THE TOTAL ANEMIA (228/417) PRESENTED THE HETEROGENOUS ERYTHROCYTE POPULATION (HIGH RDW) AND 45.3% OF THE CASES (189/417) HAD NORMAL RDW. THE MOST PREVALENT ANEMIA DURING THE YEAR 2017, OF THE TESTS PERFORMED IN THE UNIEVANGLICA CLINICAL ANALYZES LABORATORY, WAS NORMOCYTIC AND NORMOCHROMIC ANEMIA, DESPITE THE FEW STUDIES IN THE CENTRAL-WEST REGION, THE VALUE IS IN AGREEMENT WITH THE REGIONAL LITERATURE. THE SECOND MOST COMMON MORPHOLOGICAL FORM WAS MICROCYTIC, WHOSE MAIN CAUSE IS THE LOW CONSUMPTION OF FOODS RICH IN IRON. AND THE MACROCYTIC FORM WAS THE ONE WITH THE LOWEST PREVALENCE IN THE REGION.
Keywords: Hematologic Diseases. Blood. Clinical Laboratory Techniques.